2022
DOI: 10.1038/s41419-022-05307-5
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHH2 binds β-arrestin1 through its FERM domain, activates FAK/PI3K/AKT phosphorylation, and promotes the malignant phenotype of non-small cell lung cancer

Abstract: PLEKHH2 is an important FERM domain containing-protein. However, the role of PLEKHH2 in human solid tumors has not been reported yet. We report that PLEKHH2 showed enhanced cytoplasmic expression in non-small cell lung cancer (NSCLC). Its overexpression was positively correlated with high TNM stage, low differentiation, lymphatic node metastasis, and poor prognosis. In A549 and H1299 cells, high expression of PLEKHH2 significantly promoted cell proliferation, migration, invasion, and increased the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A recent study reported that PLEKHH2, a member of the pleckstrin homology domaincontaining family H, is also highly expressed in NSCLC (Wang et al, 2022b). Studies with NSCLC cells showed that high expression of PLEKHH2 facilitated cell proliferation, migration, and invasion (Wang et al, 2022b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that PLEKHH2, a member of the pleckstrin homology domaincontaining family H, is also highly expressed in NSCLC (Wang et al, 2022b). Studies with NSCLC cells showed that high expression of PLEKHH2 facilitated cell proliferation, migration, and invasion (Wang et al, 2022b).…”
mentioning
confidence: 99%
“…A recent study reported that PLEKHH2, a member of the pleckstrin homology domaincontaining family H, is also highly expressed in NSCLC (Wang et al, 2022b). Studies with NSCLC cells showed that high expression of PLEKHH2 facilitated cell proliferation, migration, and invasion (Wang et al, 2022b). Biochemical studies showed that PLEKHH2 binds to βarr1 through its FERM domain, resulting in the activation of the FAK/PI3K/AKT signaling cascade and the stimulation of NSCLC cell proliferation, migration, and invasion (Wang et al, 2022b).…”
mentioning
confidence: 99%
“…Direct interactions between the FERM domain of the plekhh2 and the focal adhesion protein Hic-5 and actin stabilize the cortical actin cytoskeleton by attenuating actin depolymerization, and are involved in the podocyte foot processes [ 69 ]. A high expression of PLEKHH2 also significantly increased the expression of proliferation- and invasion-related proteins and promoted cell proliferation, migration, and invasion [ 70 ]. PLEKHH2 variants have been associated with diabetes nephropathy, coronary artery disease and venous thromboembolism, and have interacted with antihypertensive drugs for new-onset diabetes [ 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGF-β has the ability to impact various intracellular signaling pathways, such as the VEGF and PI3K/AKT pathways, which play a crucial role in the proliferation, growth, and metastasis of lung cancer cells. They are effective therapeutic targets for lung cancer [19] . The findings indicated that the group B exhibited an increase in…”
Section: Acknowledgementmentioning
confidence: 99%